Leadership Style Policy After Acquisition; Case Study at PT. Karya Persada - Putra, Hendri Eka Jaya; Wahdi, Hilmy (Jurnal Magister Administrasi Publik, 2021)
The purpose of this research is to identify changes in the company organization of PT Karya Persada, specifically 1) Examine how the organization of PT Karya Persada has changed since the acquisition. 2. Describe the changes that have occurred. 3. ) Analyzing the relationship between changing organizational aspects at PT. Persada's work. 4). Identifying the anticipation or management strategy used by PT Karya Persada in the face of this change. This research can also academically deepen knowledge about change management, organizational culture, leadership style, and learning organizational, as well as see the extent of its application, supporting factors, and constraints that arise in its application. The descriptive qualitative research methods were used in this study. The data in this study were obtained by conducting interviews with former employees of PT. Karya Persada will go directly to take data at PT. Persada's work that has been obtained from the interview data is processed using NVivo 12 Plus Qualitative Software. According to the findings of this study, there is a change in organizational culture, such as a family-like spirit that becomes more procedural and full of control. Less discipline became much more disciplined from the start. Furthermore, a previously opaque culture has become more transparent, with clearer rewards and punishments, including at higher levels of promotion and career advancement.